Pengaruh Bimbingan Kelompok dengan Pendekatan Cognitive Behavioral Therapy (CBT) untuk Meningkatkan Kualitas Tidur Penderita Insomnia (Studi Quasi Eksperimen Pada Mahasiswa Akhir UIN Raden Fatah Palembang): Penelitian - Mulyani, Mirna Ari; Putra, Bela Janare; Fathurrahman, Muhammad (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to determine the effect of group counseling using the Cognitive Behavioral Therapy (CBT) approach in improving sleep quality among final-year students experiencing insomnia symptoms at UIN Raden Fatah Palembang. The background of this study is based on the phenomenon of poor sleep quality among university students due to academic stress and the burden of thesis completion. The research employed a quantitative approach with an experimental method and a one-group pretest–posttest design. The sample consisted of 10 students selected through purposive sampling based on the results of a sleep quality questionnaire indicating poor sleep quality. The research instrument used was a sleep quality questionnaire that had been tested for validity and reliability. Data analysis techniques included the Shapiro–Wilk normality test, homogeneity test, and Paired Sample t-Test to test the hypothesis. The results showed an increase in the average sleep quality score from 77 in the pretest to 113 in the posttest. The significance value (Sig. 2-tailed) of 0.000 < 0.05 indicates a significant difference before and after the treatment. Thus, it can be concluded that group counseling using the CBT approach has a significant effect on improving sleep quality among final-year students. These findings reinforce empirical evidence that the implementation of CBT in the context of group counseling is effective in helping students manage stress, reduce negative thoughts about sleep, and improve overall psychological well-being.